PENDISTRIBUSIAN ZAKAT DALAM MENINGKATKAN KESEJAHTERAAN MUSTAHIK DI KECAMATAN MEDAN POLONIA : (Studi Pada BKM Mesjid Agung Kota Medan) - Khairiah Nasution; Titir Nauli Siagian; Yunus Amir Husein; Yenni Samri Juliati Nasution (INTERNATIONAL, Journal of Sharia Business Management, 2026)
Zakat is a part of Islamic economics that functions to assist underprivileged communities and reduce poverty gaps. This study aims to examine how the Mosque Management Board (BKM) of the Great Mosque of Medan distributes zakat to improve the welfare of mustahik (zakat recipients) in Medan Polonia District. This research employed a descriptive qualitative method, with data collected through interviews with mosque administrators and zakat recipients, supported by observations. The results of the study indicate that the distribution of zakat goes through three stages, namely data collection, verification, and determination of recipients. The zakat distributed is generally in the form of cash assistance, depending on the total funds collected. For the mustahik, this assistance is very beneficial in helping them purchase basic necessities and reduce their living burdens, especially approaching Eid al-Fitr. However, the main obstacle faced is the limited number of muzakki (zakat payers) who channel their zakat through this mosque, resulting in limited funds being managed.